2004
DOI: 10.1017/s0950268804002201
|View full text |Cite
|
Sign up to set email alerts
|

E-mail surveys assist investigation and response: a university conjunctivitis outbreak

Abstract: A conjunctivitis outbreak affecting more than 200 individuals occurred on a university campus in Evanston, Illinois, USA, in spring 2002. An investigation was conducted jointly by the Evanston Department of Health and the Illinois Department of Public Health. A combination of e-mail and traditional telephone-based surveys demonstrated that wearing contact lenses was a risk factor for any conjunctivitis and bilateral conjunctivitis, whereas using glasses was protective. Laboratory and epidemiological evidence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…This was our first experience of using the internet in this way and was prompted by the evident computer literacy of the event participants. In common with other authors we believe our work has demonstrated that efficiency and timeliness are the most significant strengths of the method [12,13,15,16,18]. The use of email invitations and an internet-based questionnaire allowed us to rapidly and efficiently access the geographically dispersed population at minimal cost [19].…”
Section: Outcome Of the Investigationsupporting
confidence: 74%
See 3 more Smart Citations
“…This was our first experience of using the internet in this way and was prompted by the evident computer literacy of the event participants. In common with other authors we believe our work has demonstrated that efficiency and timeliness are the most significant strengths of the method [12,13,15,16,18]. The use of email invitations and an internet-based questionnaire allowed us to rapidly and efficiently access the geographically dispersed population at minimal cost [19].…”
Section: Outcome Of the Investigationsupporting
confidence: 74%
“…While some investigators have managed to obtain higher response rates using internet-based methods, these have often, but not exclusively, been on relatively small, well defined or easily accessible groups [5, 12, 13, 17, 18]. In contrast, other outbreak investigations involving larger community-based populations have obtained lower response rates than we achieved, with some as low as 11% [14, 15]. Although it is therefore possible that we have obtained biased estimate of the risks in this outbreak, we believe that the numbers involved in our investigation are sufficiently large for the overall findings to be robust.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations